2015
DOI: 10.1016/j.diamond.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of silicon doped diamond like carbon thin films on surface properties and human serum albumin adsorption

Abstract: Diamond-like carbon (DLC) coatings are useful for creating biocompatible surfaces for medical implants. DLC and silicon doped DLC have been synthesised using plasma enhanced chemical vapour deposition (PECVD). The effects of surface morphology on the interaction of human serum albumin (HSA) with doped and undoped DLC films have been investigated using a range of surface analysis techniques using Raman spectroscopy and atomic force microscopy (AFM). Raman spectra of doped DLC show that silicon doped DLC reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…It should be mentioned, that an increase of the oxygen atomic concentration with Si amount in DLC:Si films was reported by other authors, too [12,18]. In numerous studies, relatively large amounts of oxygen, comparable with the present study or even higher, were reported for both hydrogenated [18,20,21] and hydrogen-free [12,17] DLC:Si films. In other case, O atomic concentration increased for DLC:Si films deposited by plasma-enhanced chemical vapor deposition from tetramethylsilane (TMS) only in comparison with the films deposited from the mixture of C 2 H 2 and TMS [18].…”
Section: Chemical Compositionsupporting
confidence: 88%
See 2 more Smart Citations
“…It should be mentioned, that an increase of the oxygen atomic concentration with Si amount in DLC:Si films was reported by other authors, too [12,18]. In numerous studies, relatively large amounts of oxygen, comparable with the present study or even higher, were reported for both hydrogenated [18,20,21] and hydrogen-free [12,17] DLC:Si films. In other case, O atomic concentration increased for DLC:Si films deposited by plasma-enhanced chemical vapor deposition from tetramethylsilane (TMS) only in comparison with the films deposited from the mixture of C 2 H 2 and TMS [18].…”
Section: Chemical Compositionsupporting
confidence: 88%
“…It should be mentioned that such behavior was reported in numerous studies for both hydrogen-free and hydrogenated DLC films containing silicon or SiO x [8,[33][34][35][36]. G peak position downshift to 1505 cm −1 [21], 1495 cm −1 [23], 1480 cm −1 [12] and even as low as 1460 cm −1 [17,19] was reported. In those studies, the changes were explained by the increased sp 3 /sp 2 carbon bond ratio.…”
Section: Structurementioning
confidence: 52%
See 1 more Smart Citation
“…Such layers containing Si tended to increase the water contact angle, i.e., becoming more hydrophobic. A similar effect was confirmed by Ahmed et al [47]. Wettability may thus play an important role in increasing human serum albumin adsorption on the DLC:Si film surface, because a more hydrophobic surface reduces its interaction with water molecules, allowing for more direct contact with the protein.…”
Section: Contact Angle and Sfe Analysissupporting
confidence: 75%
“…The BSA molecule model is ellipsoidal with the dimensions of 4 nm × 4 nm × 14 nm 16 . According to the molecule feature, there are usually two kinds of models when the albumin monolayer is adsorbed to the material surface: side-on and end-on 17 . The thickness of the BSA-adsorbed layer showed in Fig.…”
Section: Discussionmentioning
confidence: 99%